Vermicompost and arbuscular mycorrhizal, its effect on nutrition of cocoa in greenhouse phase - Ricárdez-Pérez, Juan David; Gomez Alvarez, Regino; Alvarez-Solis, José David; Pat-Fernández, Juan Manuel; Jarquín-Sanchéz, Aarón (Ecosistemas y Recursos Agropecuarios, 2020)
Cocoa (Theobroma cacao L.) is a tropical plant with high ecological, economic and social impact in Mexico. However, its yield has decreased due to the low techniﬁcation of the crop, the advanced age of the plantations and pest attack and diseases. The objective of this study was to evaluate the microbial activity in different treatments where vermicompost and the arbuscular mycorrhizal fungus Rhizophagus intraradices were applied and to know the effects on growth and nutrition of cocoa seedlings in greenhouse phase. Vermicompost and Peat Moss substrates were used in concentrations of 25 and 50% and the Technical Instruction on Production with and without the application of the mycorrhizal fungus. Growth, plant nutrition and microbial activity were determined in each treatment. The best results were obtained in treatments with 50% vermicompost and 50% vermicompost + Peat Moss, with increases in microbial activity, foliar phosphorus and number of spores of the mycorrhizal fungus. The plants inoculated with the mycorrhiza increased their height and improved their nutritional status in greenhouse phase.